Diminished Expression of Fat and Dachsous PCP Proteins Impaired Centriole Planar Polarization in Drosophila - Garrido-Jimenez, Sergio; Roman, Angel-Carlos; Carvajal-Gonzalez, Jose Maria (Frontiers in Genetics, 2019)
Proper ciliary basal body positioning within a cell is key for cilia functioning. Centriole and basal body positioning depends on signaling pathways such as the planar cell polarity pathway (PCP) governed by Frizzled (Fz-PCP). There have been described two PCP pathways controlled by different protein complexes, the Frizzled-PCP and the Fat-PCP pathway. Centriole planar polarization in non-dividing cells is a dynamic process that depends on the Fz-PCP pathway to properly occur during development from flies to humans. However, the function of the Ft-PCP pathway in centrioles polarization is elusive. Here we present a descriptive initial analysis of centrioles polarization in Fat-PCP loss of function (LOF) conditions. We found that Fat (Ft) and Dachsous (Ds) LOF showed a marked centrioles polarization defect similar to what we have previously reported in Fz-PCP alterations. Altogether, our data suggest that centriole planar polarization in Drosophila wings depends on both Ft-PCP and Fz-PCP pathways. Further analyses in single and double mutant conditions will be required to address the functional connection between PCP and centriole polarization in flies.